Resolution of Dual Land Certificate Ownership Issued by the Head of Sukajadi Village, Hinai District, Langkat Regency - Eriska , Reda; Khalid, Khalid (Dinasti Research, 2024)
This study aims to delve into the concrete solution to the problem of duplicate land certificates originating from the Head of Sukajadi Village, Hinai District, Langkat Regency. The research method applied is a field study with a qualitative approach that prioritizes descriptive data analysis. The qualitative approach was chosen because it can provide a deep understanding of the context and dynamics that occur in this problem. The results of the study clearly show that there was negligence in the process of issuing certificates by the parties involved, such as land owners, the Land Office, and the local government. This negligence is the main root of the problem that resulted in duplicate land certificates in the area. This indicates the importance of increasing accuracy and supervision during the land certificate issuance process. In the context of resolving this problem, a comprehensive evaluation of the applicable land certificate issuance procedures is needed. This evaluation must be carried out systematically to identify weak points in the process that are the entry point for duplicate land certificates. In addition, substantive improvements to the certificate issuance procedure also need to be made as a preventive measure to avoid similar problems from recurring in the future. In addition to evaluating and improving procedures, increasing legal awareness and responsibility from all parties involved is the key to an effective resolution. This includes improving legal understanding regarding land ownership, the rights and obligations of land owners, and the responsibilities of the Land Office and the local government in the certificate issuance process. Legal education and socialization need to be improved so that the public is more aware of the importance of maintaining the validity of legal documents, including land certificates.